Decision Making Management in Increasing the Quality of Schools - Simatupang, Umy Nadrah; Awam, Rafizah; Sabandi, Ahmad (Postgraduate School, Universitas Negeri Padang, 2023)
School quality is an important issue and is of concern to every school organization in improving the quality of education, which is influenced by human resources, teachers, students, and other structural elements. The authors of this article aim to discuss ways to improve school quality through decision-making. The method used is library research, ie 1) library research in various journals and 2) source based on a review of articles and various sources, it was concluded that several things can be considered in decision-making management in maximizing school quality, namely paying attention to the decision-making system based on various adjustments to decision making the existing conditions to produce the right decision.